Hydrogen sulfide against preeclampsia exposure-induced oxidative mitochondrial damage in HTR-8/SVneo cells - Wang, Xianli; Yu, Shaokun; Jian, Yuting; Pan, Hongmin; Guo, Jiannan; Wu, Jian; Guo, Wei (Frontiers in Cardiovascular Medicine, 2022)
Extravillous trophoblast invasion disorder caused by oxidative stress is involved in the pathogenesis of preeclampsia(PE). In order to identify whether hydrogen sulfide (H2S) can prevent oxidative stress injury in extravillous trophoblasts. HTR-8/SVneo cells were detected by H2S inhibiting H2O2 induced oxidative mitochondrial damage. Reactive oxygen species (ROS) were detected, as well as malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD). JC-1 detected the potential of the mitochondrial membrane in this experiment. Then to detect the expression level of the apoptosis-inducing protein Bcl-2 associated x protein (Bax), caspase 3, p53, p-p53, the apoptosis-inhibiting protein B-cell lymphoma-2(Bcl-2), PRAP, and the mitochondria fission protein Drp1, p-Drp1. Using the CCK-8 assay, it was demonstrated that cell proliferation in the NaHS group was significantly higher than that in the Mod group, indicating that H2S may induce cell proliferation. Transwell assay elucidated that cell invasion in the NaHS group was recovered compared to the Mod group. ROS concentration no matter in cells or mitochondria was decreased by NaHS, which we could get from the comparison between the Mod group, PAG group, and NaHS group. The concentration of MDA was significantly lower in the NaHS group, and the concentration of SOD was extremely high in the NaHS group. Utilized JC-1 to detect mitochondrial membrane potential and found that cells from the NaHS group had a stable potential while cells from the Mod group and PAG group partly lost their potential, which could demonstrate that NaHS could maintain mitochondrial membrane potential. The western blot results revealed that p-Drp1 had a significant decline in the NaHS group, which means mitochondria fission was decreased in the NaHS group. The expression level of Bax and caspase 3 was significantly lower than in the Mod group and PAG group, and the expression level of Bcl-2 and PRAP was significantly higher in the NaHS group. That could prove that NaHS protect HTR-8/SVneo cell by inhibiting cell apoptosis. These promising results show that H2S elicits its effects on cell apoptosis by decreasing ROS concentration, maintaining mitochondrial membrane stability, and promoting apoptosis-inhibiting protein expression in cells.